KADERISASI FUQAHA DALAM PERKEMBANGAN HUKUM ISLAM - Muchsin, Agus (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2010)
This article elucidates the regeneration of Islamic legal scholars in the context of the development of Islamic law. Using historical approach, this study shows that fiqh as a discipline did not exist in the early phase of Islam. The term fiqh in that phase referred to its etymologic meaning, i.e., comprehension. The companion of the prophet who had in-depth comprehension of Islam was termed faqih (plural: fuqaha). So, the term fiqh in its early phase of Islam signified an overall comprehension of all the teachings of God relating to belief, law, ethics, and other aspects. The regeneration according to Islamic perspective is aimed at preparing the candidates of highly intelligent, mature leader, with high moral integrity, who will guard and develop the identity of Islam as khair ummah (the best community). Nowadays, the cadre of Islam continues to exist to maintain and develop the regeneration of Islamic legal scholars through mosques, religious organizations, and pesantren (Islamic boarding schools).